Consumer Behavior in The Digital Age: A Qualitative Analysis of Online Shopping Patterns in Indonesia - Erlangga, Heri; Setiawati, Tita; Riadi, Farid; Hindarsah, Ida; Riani, Dini (Majalah Ilmiah Bijak, 2024)
The development of digital technology has significantly changed consumer behavior, including in Indonesia. This research aims to qualitatively analyze consumer online shopping patterns in Indonesia. Using in-depth interview methods and content analysis, this research explores the factors that influence consumer decisions in online shopping, e-commerce platform preferences, as well as the challenges and obstacles they face. The research results show that ease of access, product variety and price promotions are the main factors that encourage consumers to shop online. Apart from that, trust in transaction security and product quality also plays an important role in purchasing decisions. This research also found that social media plays a significant role in influencing consumer shopping behavior through product recommendations and reviews. However, several challenges such as limited internet infrastructure and lack of technological knowledge among certain consumers remain obstacles to wider adoption of online shopping. The findings from this research provide insights for e-commerce companies and policymakers to develop more effective strategies for promoting online shopping and improving consumer experiences. This research also suggests the need for education and infrastructure improvements to support the growth of e-commerce in Indonesia.